2016
DOI: 10.24093/awej/vol7no3.12
|View full text |Cite
|
Sign up to set email alerts
|

Thai Students’ Perceptions on the Direct Vs. Indirect Written Corrective Feedback: A Thai University Context

Abstract: Feedback is an important skill and a valuable part of any language course. The term feedback has been used by various scholars to refer to both negative as well as positive error treatment in both natural settings and the instructional setting. Some researchers have raised objections to corrective use and have pointed out that it is unhelpful or even harmful for students' writing development. Yet others seem to have established evidence in support of corrective feedback. Nevertheless, very few studies have con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…On the other hand, teacher feedback, particularly circling and/or underlining written errors without any teacher's commentary was their less preference in their writing drafts. This has misled students into wrong and ambiguous ideas of generating their paragraph in English similar to Hosseiny's (2014) and Tangkiengsirisin & Kalra's (2016) findings showing that the indirect feedback made them confused when the teacher only circled or underlined their writing errors. Students no longer had any opportunities to enhance writing skills because they did not receive proper feedback at the beginning stage of writing.…”
Section: Difference Between An Implicit and An Explicit Feedbackmentioning
confidence: 94%
See 3 more Smart Citations
“…On the other hand, teacher feedback, particularly circling and/or underlining written errors without any teacher's commentary was their less preference in their writing drafts. This has misled students into wrong and ambiguous ideas of generating their paragraph in English similar to Hosseiny's (2014) and Tangkiengsirisin & Kalra's (2016) findings showing that the indirect feedback made them confused when the teacher only circled or underlined their writing errors. Students no longer had any opportunities to enhance writing skills because they did not receive proper feedback at the beginning stage of writing.…”
Section: Difference Between An Implicit and An Explicit Feedbackmentioning
confidence: 94%
“…Writing has been one of the most prominent English language skills in ESL/EFL classrooms (Ahmadi, Maftoon & Mehrdad, 2012;Fareed, Ashraf & Bilal, 2016). English writing obviously appears to be a crucial mediation to convey opinions and thoughts in literate communities and across the globe (Tangkiengsirisin & Kalra, 2016). Nonetheless, foreign language learners found that writing in English is much more difficult than other English skills (Phuket & Othman, 2015) since a good paragraph primarily needs a topic sentence, supporting ideas, and conclusion (Wirantaka, 2016).…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The results also suggested that language teachers have to consider individual learner differences. Similarly, Tangkiengsirisin and Kalra (2016) studied the perfections of Thai learners towards direct and indirect WCF. The results showed that the group which received direct CF improved significantly compared to the group which received indirect CF.…”
Section: Corrective Feedback: From 2016 To 2022mentioning
confidence: 99%